Propagación in vitro de Dalbergia congestiflora (Campincerán) a partir de estacas cultivadas en invernadero - Hernández García, Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
In this research a method of clonal propagation in vitro of Dalbergia congestiflora (campincerán) was established, culturing shoots from cuttings grown in greenhouse culture. Shooting of 20 cm cuttings was evaluate with three diameters (0.5, 1 and 1.5 cm). These were obtain from an adult individual in field, applying three rooting: IBA (indole-3-butyric acid), Auxin-F (Raizone-Plus) and Auxin-NP (Pro-root) (1, 5 and 10 ppm). Cuttings were grown in peat moss-perlite (1:1 v/v) in greenhouse conditions and under continuous irrigation with running water (n=3), evaluating the percentage of sprouting, number and length of the shoots for 45 days. At this time it was observed a greater length of the shoots (10.5 cm per cutting) with 5 ppm of Auxin-F and a greater number of shoots per cutting (11.5 shoots) with a length of 8 cm, with Auxin-NP in 5 ppm. After 5 months of culture, 66% of the cuttings with 10 ppm of Auxin-F formed 4 roots and 40% of callus. The cuttings treated with Auxin-NP were used for the establishment of in vitro for producing the largest number of explants (29 buds/stake). The in vitro establishment of D. congestiflora was achieved with the bud explants in the Murashige and Skoog (MS) culture media without growth regulators. Four aseptic treatments were utilized and an 80% survival of the explants with a loss of 20% by necrosis was obtained with the selected treatment. This consisted in treat the explants with 20% of commercial sodium hypochlorite (6% chlorine active) for 5 min, detergent hyclin (15%) more Tecto 60 (5.0 g/L) for 5 min, and finally with 20% of sodium hypochlorite more Tecto 60 (5.0 g/L) for 20 min. At 45 days after MS cultivation with 0.05 mg/L benzyladenine (BA), 75% of the explants developed an initial shoot of 0.5 cm in length with two leaves. The largest number of shoots (4.6 shoots/explant) with a length of 1.63 cm was obtained in 100% of buds grown for 45 days in MS with 1.0 mg/L BA and 0.1 mg/L naphtalenacetic acid (NAA), in this medium was also observed a high percentage of callogenesis. Organogenesis in callus was obtained in MS with 1.0 mg/L BA and 0.1 mg/L of ANA, presenting 1.4 shoots/cm2 with a length of 1.6 cm.

En la presente investigación se estableció un método de propagación clonal in vitro de Dalbergia congestiflora (campincerán) por el cultivo de brotes a partir de estacas cultivadas en invernadero. Se evaluó la brotación en estacas de 20 cm de longitud con tres diámetros (0.5, 1 y 1.5 cm). Éstas fueron obtenidas de un individuo adulto en campo, aplicando tres enraizadores: AIB (ácido indol-3-butírico), Auxina-F (Raizone-Plus) y Auxina-NP (Pro-root) (1, 5 y 10 ppm). Las estacas fueron cultivadas en turba-agrolita (1:1 v/v) en condiciones de invernadero y bajo riego continuo con agua corriente (n=3), evaluando el porcentaje de brotación, número y longitud de los brotes durante 45 días. A este tiempo se observó una mayor longitud del brote (10.5 cm por estaca) con 5 ppm de Auxina-F y un mayor número de brotes por estaca (11.5 brotes) con una longitud de 8 cm, con Auxina-NP en 5 ppm. Después de 5 meses de cultivo, el 66% de las estacas con 10 ppm de Auxina-F formaron 4 raíces y 40% de callo. Las estacas tratadas con Auxina-NP fueron utilizadas para el establecimiento in vitro, por producir el mayor número de explantes (29 yemas/estaca). El establecimiento in vitro de D. congestiflora se logró con el cultivo de yemas en medio de cultivo de Murashige y Skoog (MS) sin reguladores de crecimiento. Se aplicaron cuatro tratamientos de asepsia, obteniendo un 80% de supervivencia de los explantes y una pérdida del 20% por necrosis con el tratamiento seleccionado, consistente en tratar los explantes con hipoclorito de sodio comercial (6% cloro activo) al 20% por 5 min, detergente hyclin (15%) más Tecto 60 (5.0 g/L) por 5 min y finalmente con hipoclorito de sodio másTecto 60 (5.0 g/L) al 20%por 20 min. A los 45 días del cultivo en MS con 0.05 mg/L de benciladenina (BA), el 75% de los explantes desarrolló un brote inicial de 0.5 cm de longitud con dos hojas.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2014-2029; Campincerán; Callogénesis; Micropropagación; Yemas; In Vitro; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/197